MULTIMEDIA CREATIVE PROJECT AS A TRAINING TECHNOLOGY OF FUTURE SPECIALISTS IN THE FIELD OF MASS MEDIA - Yaroslav V. Yanenko (Інформаційні технології і засоби навчання, 2014)
The study defines the characteristics of modern creative projects as a technology of training of future specialists in the field of media, advertising and public relations. Special attention is paid to analysis of the concepts of «multimedia» and «creative project». The article offers practical examples of implementation of multimedia creative projects made by students in «Journalism» and «Advertising and public relations» of Sumy State University in the study of special subjects «Branding» and «Practice of advertising». Examples of creative jobs as a short-term creative projects in the discipline «Theory of advertising» are presented.